Modelling tools and methodologies for rapid protocell prototyping - Smaldon, James (2011)
The field of unconventional computing considers the possibility of implementing computational devices using novel paradigms and materials to produce computers which may be more efficient, adaptable and robust than their silicon based counterparts. The integration of computation into the realms of chemistry and biology will allow the embedding of engineered logic into living systems and could produce truly ubiquitous computing devices. Recently, advances in synthetic biology have resulted in the modification of microorganism genomes to create computational behaviour in living cells, so called “cellular computing”. The cellular computing paradigm offers the possibility of intelligent bacterial agents which may respond and communicate with one another according to chemical signals received from the environment. However, the high levels of complexity when altering an organism which has been well adapted to certain environments over millions of years of evolution suggests an alternative approach in which chemical computational devices can be constructed completely from the bottom up, allowing the designer exquisite control and knowledge about the system being created. This thesis presents the development of a simulation and modelling framework to aid the study and design of bottom-up chemical computers, involving the encapsulation of computational re-actions within vesicles. The new “vesicle computing” paradigm is investigated using a sophisticated multi-scale simulation framework, developed from mesoscale, macroscale and executable biology techniques.